2018
DOI: 10.1016/j.athoracsur.2017.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Failure to Rescue After Esophagectomy

Abstract: Nearly 6% of patients who have a major complication after esophagectomy do not survive to discharge. Age greater than 75 years, black race, American Society of Anesthesiologists class 4 or 5, and complications related to major infection or organ failure predict FTR. Further research is necessary to investigate how these factors affect survival after complications in order to improve rescue efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…This latter scenario is in line with the concept of rescuing patients from severe complications. From this perspective, other factors beyond the occurrence of a severe complication such as ML need to be considered: for example, the surgeon and hospital volume[29], the nurse-to-patient ratio, and the multidisciplinary approach to the treatment of the complication can definitely be important in reducing the mortality rate[30].…”
Section: Discussionmentioning
confidence: 99%
“…This latter scenario is in line with the concept of rescuing patients from severe complications. From this perspective, other factors beyond the occurrence of a severe complication such as ML need to be considered: for example, the surgeon and hospital volume[29], the nurse-to-patient ratio, and the multidisciplinary approach to the treatment of the complication can definitely be important in reducing the mortality rate[30].…”
Section: Discussionmentioning
confidence: 99%
“…As hypothesized, esophagectomy induced a rapid drop of albumin, 9,10,12,12,17 which appeared more pronounced in patients who subsequently developed major complications (Figure 1). Present analyses established a cut‐off of ∆Alb at 11 g/L.…”
Section: Discussionmentioning
confidence: 57%
“…Although minimally invasive esophagectomy (MIE) may improve short‐term outcomes, 5,6 esophagectomy remains associated with substantial rates of mortality and severe morbidity, which may compromise long‐term survival 7,8 . Early identification of postoperative complications is of utmost importance, as their systemic impact and subsequent risk of mortality may be reduced if they are promptly detected and treated, especially in elderly or frail patients 9 . In this context, the identification of accurate biomarkers able to predict adverse outcomes early in the postoperative course is of high clinical relevance, as it may help to better anticipate patients’ care and to improve their outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our results also showed no association between FFM and short‐term SWL. Patients with an ASA score of 3–4 always suffer from severe systemic diseases and dysfunction before surgery, which appear to affect not only perioperative complications and mortality but also postoperative weight recovery . Previous studies have also investigated the risk factors for SWL after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an ASA score of 3-4 always suffer from severe systemic diseases and dysfunction before surgery, which appear to affect not only perioperative complications and mortality but also postoperative weight recovery. [41][42][43] Previous studies have also investigated the risk factors for SWL after esophagectomy. Park et al reported that preoperative weight and postoperative VCP were independent risk factors for weight loss > 10% of PWL one year after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%